A família e a criança no psicodiagnóstico infantil: estudo em uma clínica-escola de São Paulo - Santa-Rosa, Ednilton José (2008)
The present study has the objective to verify the idea of familys contained in the infantile psychodiagnostics realized in a clinic-school at São Paulo city by psychologist trainee. It was searched twenty-one final reports of psychodiagnostics, made between 2003 and 2004, that had determined the leading of children to the psychotherapy. From the selected reports were extracted some elements, such as, terms, concepts, expressions, and explanations related to the family in the child education. These elements allowed us to separate the subjects in two categories named as Family Linking and Children Care. In the first category, we allocated the psychodiagnostic comprehension of indicators referred to the way the linking between the child and each one of the family members. It was allocated in the second category the indicators concerned to family members conduction when it affects the children s feelings of safe, protection, and development. The conceptual base of the searching is pertinent to the critical theory of the society; especially the discussions related to family, ideology, psychology and technique. It was concluded that a family representation constituted by individuals, who are linked with defined rules such as father, mother and children, bases the notions of family. The function, performed by the family, of child care is conditioned to the adjustment of the family members, more specifically the parents, to the their rules functions. Nevertheless, it is not considered duly the social factors that imply in the family constitution